Improved controlled flavor formation during heat-treatment with a stable Maillard reaction intermediate derived from xylose-phenylalanine. (15th January 2019) - Cui, Heping; Yu, Jingyang; Xia, Shuqin; Duhoranimana, Emmanuel; Huang, Qingrong; Zhang, Xiaoming
Highlights: The flavor of Maillard reaction products (MRPs) solution was unstable during storage. The size of particles in MRPs increased dramatically after storage or heat treatment. The Maillard reaction intermediate (MRI) was heat labile but stable during storage. The heated MRI showed flavor fingerprints as the MRPs before heat treatment. The MRI has tremendous capacity to be applied as a potential alternative to MRPs. Abstract: The Maillard reaction intermediate (MRI) and Maillard reaction products (MRPs) derived from xylose (Xyl) and phenylalanine (Phe) were prepared, then stored at 25 °C for 60 days. After storage, the contents of flavor compounds and the clarity of MRPs solution decreased, and the apparent Z-average hydrodynamic diameter (Dh ) of particles in the solution increased from 149 to 439 nm. However, the MRI solution remained transparent during storage. The concentration of MRI only decreased by 6.49%, and A294 of the solution increased slightly yet A420 remained stable. Numerous flavor compounds in MRPs decreased during heat treatment, meanwhile the cross-linking and aggregation of MRPs were intensified, and the particles' Dh increased to micron level. The heated MRI solution showed a similar appealing profile and flavor fingerprints as the MRPs solution before heat treatment. Controlled formation of flavors from MRIs is proposed to be used as potential alternative to the existing Maillard flavorings.